Sociocultural paradigm of the totalitarian and indifferent in the plastic arts of Ukraine in the 1940s-1960s - Олексій Роготченко (Сучасне мистецтво, 2017)
In the 1940s and 1960s, the official style of socialist realism was established in Ukrainian sculpture, as well as in other types of subspecies and directions of fine art. The works of Ukrainian sculpture фке of this period allow us to conclude that this kind of art was the most related to the totalitarian manifestations of the plastic workshop of pre-war Germany and Russia. The task of sculptural works was to educate a new generation of Soviet people and to perpetuatе the feats. So, we can state that from the second half of the 1930s the direction of legal development was finally formed in the Ukrainian Soviet sculpture art. The foundations of socialist realism were primarily supported by the achievements of Russian classicism and realistic traditions in Roman imperial plastics. The rigid normativity of use of officially offered samples in creative sculptural works in the conditions of ideological totalitarian pressure leads to deformation of plastic thinking